The Work of Russian Choreographers in Macedonia. Preserving the Ballet Legacy - Zdravkova-Djeparoska, Sonja (Philological Faculty, Lomonosov Moscow State University, 2017)
The genesis of ballet art in Macedonia is assiciated with the initial forms of stage performances such as Dionysias festivals and the ﬁ rst theater plays, what is conﬁ rmed by the discovered archaeological localities and artefacts. But the actual projected development of the ballet in Macedonia started only in the middle of the 20th century, more precisely after 1949 and continues to the present. The foundation of this art was laid due to the formation of a ballet ensemble, educational institutions and the new repertoire. The Russian artists, who worked in Macedonia at different times, were the major contributors to the professional growth of the troupe. Three choreographers must be especially emphasize: Nina Kirsanova, Yuri Mjachin and Mikhail Krapivin, and their work in Macedonia is analized. It is connected with several segments – choreography, ballet repetition, education. This text deals with the analysis of a speciﬁ c group that belongs to the classical ballet legacy. These are masterpieces that have kept their choreography almost unchanged form since the 19th century, but at the same time they represent a synonym of the ballet art – “Swan Lake”, “Sleeping Beauty”, “Raymonda”, “Giselle” and others. They are a measure of the maturity and quality of a ballet troupe. The Macedonian ballet pays special attention and embeds it in its repertoire from the very beginning. The three mentioned choreographers are the most important in the staging and adequate preparation of the ballets of the group. They staged the “Sleeping Beauty”, “Don Quixote”, “Raymonda”, “Nutcracker”, “Copellia”, “Esmeralda” on the Macedonian scene. Their work was characterized by a high professionalism and a devotion to their work. The result are the performances that have marked the Macedonian ballet and remained for dozens of years on the repertoire.
Работата на руските кореографи во Македонија. Зачувување на балетското наследство /Работа русских хореографов в Македонии. Сохранение наследия балета
Keywords: dance, ballet, classical ballet legacy, choreography, Macedonia